Development Emotional Social in Parental Involvement of Students in Elementary Schools - Acoci, Acoci (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
The aim of this research is to determine social emotional development in parental involvement of students in elementary schools. Research conducted attempts to clearly describe parental involvement in social emotional development at Wameo 2 State Elementary School, with a formula that is not expressed in numbers. Data collection techniques used in this research are interview and observation techniques. The data analysis technique used includes 3 stages, namely data reduction, data display, and verification or drawing conclusions. The results of this research show that 1) Parental involvement in children's social emotional development through parenting, guiding children at home can be obtained, 2) Parents usually advise them not to play during breaks or during the day. Play time with friends is usually allowed in the afternoon, 3) Parental involvement is usually giving permission to children and preparing equipment as well as encouraging and encouraging them to provide maximum results, 4) Parental involvement in giving attention to their children is usually done , always remind children to always study before going to bed, 5) Usually parents are always directly involved in school activities, but when we are busy, we as parents cannot be directly involved in school activities or children's activities at home.